Delay and disruption claims in construction a practical approach - Haidar, Ali (ICE, 2011)
Drawing on their experience, the authors outline a practical approach to the presentation of delay and disruption claims in construction within a legal, contractual and technical framework. Detailed case studies are used to describe the different problems that can be encountered.